Catechol oxidase activity of comparable dimanganese and dicopper complexes - McDonald, Aidan (My University, 2018)
Synthetic CuII2 complexes have been widely investigated as model systems for catechol oxidase enzymes. The catechol oxidase reactivity of MnII2 complexes has been less explored, and the effect of metal substitution in catecholase mimics has not been explored. A series of MnII2 and CuII2 complexes supported by the same poly-benzimidazole ligand framework have been synthesised and investigated in catecholase activity in acetonitrile medium using 3,5-di-tert-butylcatechol (3,5-DTBC) as a substrate. The CuII2 complexes proved to be good catechol oxidase mimics with moderate kcat values (∼45 h−1). The kinetic parameters for MnII2 complexes exhibited lower kcat values (∼8–40 h−1) when compared to the CuII2 complexes. Our findings demonstrate that later transition metals supported by relatively electron rich ligands yield the highest kcat values for catechol oxidation.
PUBLISHED
Keywords: Catechol oxidase; Dimanganese complexes; Dicopper complexes